Principal Leadership Strategies to Improve Education Re-port Outcomes: A Case Study of SD Inpres Sanrangan - Munandar Munandar; Muh. Yunus; Nurdin Nurdin (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the principal's strategy in utilizing Education Report Card data as a basis for planning school quality improvement at the Sanrangan Elementary School Technical Implementation Unit (UPT SD Inpres), Pallangga District, Gowa Regency, and to describe the principal's strategy in implementing academic supervision and teacher mentoring to improve the achievement of Education Report Card indicators at the UPT SD Inpres Sanrangan , Pallangga District, Gowa Regency. This study uses a qualitative approach with descriptive methods. The research subjects include the principal, 3 lower grade teachers, and 3 upper grade teachers. Data collection techniques are carried out through in-depth interviews, observations, and documentation studies. Data analysis is carried out systematically through the stages of data reduction, data presentation, and drawing conclusions with data validity tests using source and technique triangulation. The results of the study indicate that the principal's strategy in utilizing Education Report Card data is carried out through collaborative analysis of school achievement indicators with teachers, setting improvement priorities based on the school's real needs, and integrating the analysis results into school quality improvement program planning. In addition, the principal's strategy in implementing academic supervision and teacher mentoring is implemented in a planned and sustainable manner by referring to Education Report Card indicators that still need to be improved. Coaching-based supervision, providing constructive feedback, and mentoring in improving learning planning and implementation have been proven to contribute positively to improving teacher competency and have an impact on improving the achievement of Education Report Card indicators at the UPT SD Inpres Sanrangan, Pallangga District, Gowa Regency.